2015
DOI: 10.17221/258/2014-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative activity of promising yeasts for cereal-based beverages using CO<sub>2</sub> headspace analysis

Abstract: Casanova F.P., Bevilacqua A., Petruzzi L., Sinigaglia M., Corbo M.R. (2015): Fermentative activity of promising yeasts for cereal-based beverages using CO 2 headspace analysis. Czech J. Food Sci., 33: 8-12.This article proposes an approach based on the evaluation of CO 2 produced by Saccharomyces cerevisiae var. boulardii, Kluyveromyces lactis × Saccharomyces cerevisiae, Saccharomyces pastorianus var. pastorianus, Kazachstania exigua, as a function of different media (laboratory media with glucose and maltose)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Casanova et al . () concluded that S. boulardii (ATCC MAY‐796) generates higher CO 2 when cultured on YPG (Yeast Peptone Glucose) broth and malt extract as compared to other health‐promoting yeasts such as Saccharomyces pastorianus , Kazachstania exigua and Kl. lactis .…”
Section: Nutritional and Nutraceutical Implications Of S Boulardii Imentioning
confidence: 99%
See 1 more Smart Citation
“…Casanova et al . () concluded that S. boulardii (ATCC MAY‐796) generates higher CO 2 when cultured on YPG (Yeast Peptone Glucose) broth and malt extract as compared to other health‐promoting yeasts such as Saccharomyces pastorianus , Kazachstania exigua and Kl. lactis .…”
Section: Nutritional and Nutraceutical Implications Of S Boulardii Imentioning
confidence: 99%
“…In this way, the fermentative activity of S. boulardii has been proposed for the elaboration of cereal-based fermented beverages mainly due to its ability to generate high amounts of CO 2 . Casanova et al (2014) concluded that S. boulardii (ATCC MAY-796) generates higher CO 2 when cultured on YPG (Yeast Peptone Glucose) broth and malt extract as compared to other health-promoting yeasts such as Saccharomyces pastorianus, Kazachstania exigua and Kl. lactis.…”
Section: Saccharomyces Boulardii In Beveragesmentioning
confidence: 99%